Pengaruh Kompetensi Digital dan Kapabilitas Adaptif terhadap Kinerja Pegawai BKPSDM Jember dengan Employee Engagement sebagai Variabel Intervening - Hasminanda Yuniasari; Trias Setyowati; Ni Nyoman Putu Martini (Journal Of Administration and Educational Management (ALIGNMENT), 2026)
This study aims to analyze the influence of digital competence and adaptive capabilities on employee performance at the Jember Regency Human Resources Development Agency (BKPSDM), with employee engagement as an intervening variable. The research method used a descriptive quantitative approach using a census technique involving 65 civil servants at the Jember Regency Human Resources Development Agency (BKPSDM). Data analysis used Partial Least Squares (PLS)-based Structural Equation Modeling (SEM). The results show that digital competence and adaptive capabilities significantly influence employee engagement, digital competence and employee engagement significantly influence employee performance, while adaptive capabilities do not directly influence performance. However, digital competence and adaptive capabilities significantly influence performance through employee engagement as a mediating variable. The conclusion is that employee engagement plays a key role in transforming digital competence and adaptive capabilities into improved employee performance. Therefore, simultaneously strengthening digital competence, adaptive capabilities, and engagement-enhancing strategies are necessary to optimize civil servant performance in the era of digital transformation.   Keywords: Digital Competence, Adaptive Capabilities, Employee Engagement, Employee Performance, Digital Transformation